The future of planetary defense. Issue 4 (20th April 2017) - Mainzer, A.
Abstract: Asteroids and comets have impacted Earth in the past and will do so in the future. While the frequency of impacts is reasonably well understood on geologic timescales, it is difficult to predict the next sizeable impact on human timescales by extrapolation from population statistics alone. Fortunately, by identifying and tracking individual objects, we can make precise predictions of any potential close encounters with Earth. As more advance notice is provided, the range of possible mitigation options expands. While the chance of an impact is very small, the potential consequences can be severe, meaning that sensible risk reduction measures should be undertaken. By implementing surveys, the risk of an unforeseen impact can be greatly reduced: the first step is finding the objects. Fortunately, the worldwide community of professional and amateur astronomers has made significant progress in discovering large near‐Earth objects (NEOs). More than 95% of NEOs capable of causing global devastation (objects larger than ~1 km in diameter) have been discovered, and none of these pose an impact hazard in the near future. Infrastructure is in place to link observations and compute close approaches in real time. Interagency and international collaborations have been undertaken to strengthen cooperative efforts to plan potential mitigation and civil defense campaigns. Yet much remains to be done. Approximately 70% of NEOs larger than 140 m (large enough to cause severe regional damage) remain undiscovered. With the existing surveys, it will take decades to identify the rest. Progress can be accelerated by undertaking new surveys with improved sensitivity. Plain Language Summary: Asteroids and comets have impacted Earth in the past and will do so in the future. Fortunately, by identifying and tracking them, we have the ability to predict any potential close encounters with Earth. By observing the sky repeatedly to search for near‐Earth objects, the risk of an unforeseen impact can be greatly reduced; the first step is finding them. While much progress has been made by the astronomical community, much work remains to be done. About 70% of the near‐Earth objects large enough to cause severe regional damage have yet to be discovered. Without investment in advanced search systems, it will take many decades to find these objects. While the chance of an impact is small, the consequences can potentially be severe, so reasonable measures (such as finding, tracking, and characterizing the asteroids) should be undertaken. Key Points: Potential asteroid and comet impacts can be predicted if we identify and track these objects Identifying any potential impacts early simplifies mitigation strategies and provides more options While the chance of an impact is low, the consequences can be severe, so a reasonable campaign should be undertaken to find them